HPLC-fluorescence detection method for determination of key intermediates of the lincomycin biosynthesis in fermentation broth - Kameník, Zdenek; Kopecký, Jan; Marecková, Markéta; Ulanová, Dana; Novotná, Jitka; Pospísil, Stanislav; Olsovská, Jana (Analytical and bioanalytical chemistry, 2009)
The biosynthetic pathway of the clinically important antibiotic lincomycin is not known in details. The precise knowledge of the lincomycin biosynthesis is a prerequisite for generation of improved derivatives by means of combinatorial genetics. Methods allowing determination of the key intermediates are very important tools of the pathway investigation. Two new high-performance liquid chromatography methods with fluorescence detection for determination of lincomycin precursors in fermentation broth of Streptomyces lincolnensis and its lincomycin nonproducing mutants were developed. The first one enables simultaneous analysis of methylthiolincosamide (MTL) and N-demethyllincomycin (NDL), whereas the second one is suitable for 4-propyl-L-proline (PPL) assay. Both methods are based on the pre-column derivatization: MTL and NDL with 4-chloro-7-nitrobenzofurazan; PPL with o-phthaldialdehyde. The methods were validated with lower limit of quantification values of 2.50, 3.75, and 3.75 microg ml(-1) for MTL, NDL, and PPL, respectively. The inter- and intra-day accuracies and precisions were all within 12%. Stability of oxidized and derivatized analytes was investigated.
Keywords: Amides; sulfhydrylové sloučeniny; Streptomyces; vysokoúčinná kapalinová chromatografie; molekulární struktura; Lincomycin; Molecular Structure; Proline; prolin; reprodukovatelnost výsledků; fermentace; Reproducibility of Results; Chromatography, High Pressure Liquid; Fluorescence; amidy; Sulfhydryl Compounds; linkomycin; Fermentation; fluorescence